Prohibiting tubal ligations in California’s correctional facilities: understanding the impact of California Senate Bill 1135 - Rachel Wallace; Vrindavani Avila; Jennifer Elyse James (Health & Justice, 2026)
Abstract California has a long history of forced sterilizations in state institutions. While the California Eugenics Program ended in 1979, involuntary sterilization continued in California State Prisons into the 2010s. In 2014, California State Senate Bill 1135 banned sterilizations for the purpose of birth control in correctional facilities. We used publicly available data to assess if these prohibitions and procedural changes had the intended result of stopping sterilization for the purpose of birth control in California prisons and jails. Data shows that tubal ligations, which are intended for the purpose of birth control, are still being performed on incarcerated people across the state. Further, these sterilizing procedures are being performed on minoritized incarcerated people in women’s prisons and jails at disproportionately high rates.